Análise do Ambiente Organizacional de Aprendizagem (AMORA) em Startups - Nascimento Júnior, Cícero Hermínio do (2025)
Abstract: This research examined the configuration of Organizational Learning Environments (ORLEEN) in startups, aiming to investigate their structure, characterize their dimensions, and identify limiting and facilitating factors. Through a multiple case study of three startups, using semi-structured interviews and observations of virtual meetings as data collection procedures, it was found that ORLEEN is structured through interaction mechanisms such as meetings, informal gatherings, and communication tools, which vary according to the startups' objectives and lifecycle stage. Additionally, five interrelated dimensions of ORLEEN in startups were characterized: human (mentoring, autonomy, feedback), relational (balance between internal communication and external networks), strategic (clear goals, market adaptation), innovation (experimentation and collaborative networks), and procedural (documentation and standardization). The results also revealed that practices vary according to the lifecycle stage (ideation, operation, growth, scaling), with facilitators including direct collaboration, digital tools, and process institutionalization, and limiting factors such as resource scarcity, disorganized communication, and isolation in telework. This study advances the understanding of the interaction between ORLEEN dimensions and the role of digital technologies in learning. It also provides guidelines for managers to structure ORLEEN by aligning learning with organizational strategies. Limitations include participant availability and challenges in data collection. Finally, future research is suggested to develop ORLEEN assessment tools and conduct quantitative studies to expand on these findings.